THE INFLUENCE OF BCG VACCINATION ON THE STRUCTURE OF CLINICAL FORMS OF TUBERCULOSIS IN CHILDREN FROM THE FOCI OF INFECTION AND FROM UNSPECIFIED CONTACT FOR TUBERCULOSIS - U.YU. SIRODJIDINOVA; O.I. BOBOKHOJAEV; K.I. PIROV; D.M. KOSIMOVA (Avicenna Tajik State Medical University, 2018)
Objective: To study the frequency of detection of severe forms of tuberculosis in vaccinated and unvaccinated BCG vaccine in children from foci of infection. Methods: There were 279 children with tuberculosis from the foci of infection: 178 (group I) of unvaccinated BCG and 101 (group II) vaccinated with BCG vaccine. In turn, these two groups were divided into two subgroups: non-vaccinated children from foci of infection (Ia) and unvaccinated children with unidentified contact (Ib) and vaccinated children from foci of infection (IIa) and with unidentified contact (IIb). An assessment was made of the forms of the disease, the frequency and nature of the complicated course of tuberculosis in vaccinated and non-vaccinated children. Results: Severe forms such as tuberculous meningitis and disseminated tuberculosis were more likely to occur in the group of children not vaccinated with BCG vaccine at birth - 17.2% (p<0.05 compared with the group of vaccinated children). In vaccinated children, tuberculosis meningitis was established in 5.6%, and in non-vaccinated patients, this age group is almost twice as likely (9.3%). Disseminated pulmonary tuberculosis was detected in non-vaccinated children under the age of 6 years in 10.0% of cases and in one vaccinated child (2.1%). In children aged 7 to 17 years, these rates were 7.4% and 5.6% respectively. In vaccinated children, up to six years of age were established in 80.9% of all cases of tuberculosis, primary tuberculosis complex (29.8%) or tuberculosis of the intrathoracic lymph nodes (51.1%). Conclusion: Thus, it can be argued that within six years after vaccination persists the body's ability to resist tuberculosis infection and in case of disease, severe forms of tuberculosis do not occur in vaccinated children. At the same time, as the BCG vaccine expires, the number of severe and common forms of tuberculosis increases. Therefore, the need for vaccination with BCG vaccine is evident, to prevent severe forms of the disease including such severe form of the disease, as tuberculous meningitis.